Análisis de la radiación solar para determinar un sistema fotovoltaico que permita abastecer la demanda eléctrica de la comuna Wamac Urco, parroquia Tarqui, provincia de Pastaza - Peña Narváez, Alex Javier (2016)
This project analyzes foundation of photovoltaic systems, its functions, its classifications and its constituent parts. This study focuses primarily on a system of autonomous generation from solar energy. Converting solar energy to electrical energy by the use of photovoltaic cells is indicated in the development of this project. The research method that was used consists of a combined modality, which a documentary study and practical applicative parts were required in the environment that the study unfolds. Once, solar radiation was evaluated in the study site, with the obtained information, the energy from 10:00 am to 2:00 p.m. was determined in the system which reaches a maximum of 4078.5 [W / m² / día], with highs at or above 1078 irradiance [W / m²], the photovoltaic system works from 8 am to 5 p.m.